The roles of statistics on Twitter in improving footballers performance / Muhammad Shahrin Aizat Noorshahrizam…[et.al] - Noorshahrizam, Muhammad Shahrin Aizat; Rafiee, Mohd Irfan Zafran; Zakaria, Wan Syabil Asyraaf; Ahmad, Muhammad Haliq; Khairulanuar, Noramirul Shafiq; Bahanurdin, Nur Syahirah (Faculty of Communication and Media Studies, 2016)
Statistics on Twitter can holds considerable potential in exposing footballer’s performance. In exposing footballers performance to the public, social media like Twitter can be a very good platform on it because it delivers direct statistics and current performance of the players to the public especially for football fans. The use of statistics of Twitter can improving the footballers performance by exposing them their real match statistics so that they can do a change on which technique that they are weak to perform much better in the next game. The goal of this research is to study the role of statistics on Twitter in improving footballer’s performance. This research is using the qualitative research method. An interview has been made to six informants to get the result of this research. All the informants are footballers from different background. The study found that the statistics on Twitter is helping in promoting footballers and helping them in improving their performance.